Analisis Struktur C-Hook SWL 30 Ton Menggunakan Metode Elemen Hingga - Dymaseka Nasbih Sabbilli; Pranowo Sidi; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
In this study, C-Hook construction analysis with SWL capacity of 30 tons will be conducted by comparing AISI 1020, ST-52 DIN 17100, ASTM A572, materials to determine the strength of CHook structure. The analysis process will use FEM (fenite element methods) approach using FEMbased software. The validity of the simulation results is carried out on the value of the result of the von misses voltage, and deflection. Validation of simulation results is done by manual calculation. The load used is 30 tons. From the results of the analysis it is known that the voltage that occurs in the loading of 30 tons in AISI 1020 material is 164,23062 Mpa, the voltage that occurs in the loading of 30 tons in ASTM A572 material is 164,32478 Mpa, and the voltage that occurs in the loading of 30 tons in the material ST52 DIN 17100 is 164,32195 Mpa. The results of the deflection analysis that occurred in the material AISI 1020 is 10,497 mm, the analysis of deflections that occurred in ASTM A572 materials is 10,695 mm, and the results of the deflection analysis that occurred in the material ST52 DIN 17100 is 10,252 mm. From the results of deflection analysis on all three materials are still below the limit, so the construction of C-Hook can be said to be safe. Based on the results of the design that has been done, it can be concluded that the material ST52 DIN17100, is the best choice and has high security to produce C-Hook.